Periodization and block periodization in sports: emphasis on strength-power training-a provocative and challenging narrative: erratum - Stone, M. H.; Hornsby, W. G.; Haff, G. G.; Fry, A. C.; Suarez, D. G.; Liu, J.; Gonzalez-Rave, J. M.; Pierce, K. C. (The Journal of Strength and Conditioning Research, 2021)
In the "Periodization and Block Periodization in Sports: Emphasis on Strength-Power Training-A Provocative and Challenging Narrative,"1 Dr. Haff's address should have stated "Western Australia" (not Washington) and Line 5 of the Abstract should have stated "Periodization deals with the macromanagement of timelines…," not micromanagement.